Analysis of Environmental Literacy in Students of the Social Studies Study Program UIN Kiai Haji Achmad Siddiq Jember: Analisis Literasi Lingkungan Pada Mahasiswa Program Studi Tadris IPS UIN Kiai Haji Achmad Siddiq Jember - Rachma Dini Fitria; Moh Barirul Umam (Chalim Journal of Teaching and Learning, 2025)
This study aims to understand the level of environmental literacy among students in the Social Studies Education Program at UIN Kiai Haji Achmad Siddiq Jember who have completed the course "Environmental Education and Sustainable Development." The research employed a quantitative descriptive method, using a questionnaire as the instrument to measure environmental literacy. The subjects of the study were selected through random sampling, involving 30 students from the total population. The level of environmental literacy was analyzed through four key aspects: environmental knowledge, Environmental attitudes, Cognitive skills, and environmentally responsible behavior. Based on the results of data processing and analysis, it is concluded that environmental literacy falls into the medium category. The average score for environmental knowledge was 47.63 (categorized as high). The score for environmental attitude was 16.46 (categorized as moderate). The score for cognitive skills was 15.5 (categorized as moderate). The score for environmentally responsible behavior was 33.93 (categorized as moderate). In general, the students' level of environmental literacy falls within the moderate category. These findings suggest that strengthening environmental literacy among students is necessary through innovative learning methods, enabling them to achieve a high level of environmental literacy. Family and environmental factors also play a significant role in fostering the development of environmentally conscious attitudes and strong environmental stewardship skills among university students.